2002
DOI: 10.1128/mcb.22.9.2928-2938.2002
|View full text |Cite
|
Sign up to set email alerts
|

p53 Is Necessary for the Apoptotic Response Mediated by a Transient Increase of Ras Activity

Abstract: The tumor suppressor p53 eliminates cancer-prone cells via multiple mechanisms, including apoptosis. Ras elicits apoptosis in cells after protein kinase C (PKC) downregulation. However, the role of p53 in Rasmediated apoptosis has not been fully investigated. Here, we demonstrate that mouse fibroblasts that express wild-type p53 are more susceptible to apoptosis elicited by PKC inhibition if Ras is transiently expressed or upregulated as opposed to stably expressed. In the latter case, p53 is frequently mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Our previous studies also demonstrated cooperation between oncogenic Ras and PKC. For instance, when endogenous PKC activity is suppressed, the increase in Ras activity is capable of inducing apoptosis in various types of cells, including lung cancer cells (20,40). In this investigation, we again showed such cooperation; after the ablation of PKC activity by GO6976, there were no MTX-resistant colonies observed from nicotinetreated RLE/E6 cells as well as no colonies formed in soft agar.…”
Section: Discussionsupporting
confidence: 55%
“…Our previous studies also demonstrated cooperation between oncogenic Ras and PKC. For instance, when endogenous PKC activity is suppressed, the increase in Ras activity is capable of inducing apoptosis in various types of cells, including lung cancer cells (20,40). In this investigation, we again showed such cooperation; after the ablation of PKC activity by GO6976, there were no MTX-resistant colonies observed from nicotinetreated RLE/E6 cells as well as no colonies formed in soft agar.…”
Section: Discussionsupporting
confidence: 55%
“…Suppression of JNK abolishes this phosphorylation, and partially blocks the apoptotic process mediated by a transient increase of Ras activity. She concluded that different mechanisms are used by short-and long-term activation of Ras to initiate apoptosis and that the status of p53 may contribute to such differences (30).…”
Section: Stress Signaling In Apoptosismentioning
confidence: 99%
“…[21][22][23][24][25][26]. Therefore, we asked what effect the expression of oncogenic Ras would have on the cell death that results from functional loss of Rb family members, an essential step in tumorigenesis.…”
Section: Oncogenic Ras Protects Against Loss-of-rb-mediated Cellmentioning
confidence: 99%